2011
DOI: 10.1136/annrheumdis-2011-200022
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of capillaroscopic skin ulcer risk index in systemic sclerosis: a multicentre validation study

Abstract: The role of CSURI was confirmed in detecting scleroderma patients with a significantly high risk of developing digital ulcers within the first 3 months from NVC evaluation. CSURI is the only method validated to predict the appearance of digital ulcers and its introduction into routine clinical practice might help optimise the therapeutic strategy of these harmful SSc complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 16 publications
1
81
0
10
Order By: Relevance
“…Indeed, some studies have shown that the late NVC pattern was predictive of the further development of severe peripheral vasculopathy and pulmonary vascular disease (14,20,21), and Sebastiani et al (22,23) showed that capillary loss, one of the main characteristics of the late NVC pattern, was the most relevant parameter to evaluate the risk of developing new digital ulcers of the capillaroscopic skin ulcer risk index formula.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown that the late NVC pattern was predictive of the further development of severe peripheral vasculopathy and pulmonary vascular disease (14,20,21), and Sebastiani et al (22,23) showed that capillary loss, one of the main characteristics of the late NVC pattern, was the most relevant parameter to evaluate the risk of developing new digital ulcers of the capillaroscopic skin ulcer risk index formula.…”
Section: Discussionmentioning
confidence: 99%
“…Ein weiterer Index CSURI (capillaroscopic skin ulcer risk index) soll mit hoher Sensitivität und Spezifität bei Patienten mit SSc das Risiko abschätzen, digitale Ulzerationen zu entwickeln [12]. Der prädiktive Wert des CSURI wurde in einer größeren prospektiven multizentrischen Folgestudie bei einem größeren Patientenkollektiv bestätigt [13]. Einen vereinfachten Algorithmus zur Risikoabschät-zung entwickelten Ingegnoli et al [14] Nicht zuletzt führten die Studienergebnisse der letzten Jahre dazu, dass bei der Consensus-Konferenz der European League Against Rheumatism (EULAR) Scleroderma Trial and Research group (EUSTAR) ein pathologisches Kapillarmuster, neben "puffy fingers", Sklerodaktylie, Raynaud-Syndrom Tabelle 2 Kapillarmikroskopische Muster nach Cutulo et al [7] und Stadien der deutschen Arbeitsgruppe "Kapillarmikroskopie" [9].…”
Section: Systemische Sklerodermieunclassified
“…The best prediction of digital ulceration is provided by the CSURI [15,75]. The predominant item of this score is the capillary density, which can be assessed easily and reproducibly.…”
Section: Usefulness Of Capillaroscopic Scoresmentioning
confidence: 99%
“…For example, in defi ning capillary density, Sebastiani et al counted every crus of the capillary in 1 mm, even in the case of elongations with a loop-whole appearance, which results in an overestimation of capillary density. They also measured the maximal total capillary diameter in the case of ectasia, resulting in an overestimation of giant capillaries [15,16].…”
Section: Normal and Single Pathologic Fi Ndingsmentioning
confidence: 99%